The Southwest Pacific Ocean circulation and climate experiment (SPICE). Issue 11 (19th November 2014) - Ganachaud, A.; Cravatte, S.; Melet, A.; Schiller, A.; Holbrook, N. J.; Sloyan, B. M.; Widlansky, M. J.; Bowen, M.; Verron, J.; Wiles, P.; Ridgway, K.; Sutton, P.; et al.
Abstract The Southwest Pacific Ocean Circulation and Climate Experiment (SPICE) is an international research program under the auspices of CLIVAR. The key objectives are to understand the Southwest Pacific Ocean circulation and the South Pacific Convergence Zone (SPCZ) dynamics, as well as their influence on regional and basin‐scale climate patterns. South Pacific thermocline waters are transported in the westward flowing South Equatorial Current (SEC) toward Australia and Papua‐New Guinea. On its way, the SEC encounters the numerous islands and straits of the Southwest Pacific and forms boundary currents and jets that eventually redistribute water to the equator and high latitudes. The transit in the Coral, Solomon, and Tasman Seas is of great importance to the climate system because changes in either the temperature or the amount of water arriving at the equator have the capability to modulate the El Niño‐Southern Oscillation, while the southward transports influence the climate and biodiversity in the Tasman Sea. After 7 years of substantial in situ oceanic observational and modeling efforts, our understanding of the region has much improved. We have a refined description of the SPCZ behavior, boundary currents, pathways, and water mass transformation, including the previously undocumented Solomon Sea. The transports are large and vary substantially in a counter‐intuitive way, with asymmetries and gating effects that depend on time scales. This paper provides a review of recent advancements and discusses our current knowledge gaps and important emerging research directions.